The concurrent effects of strike pattern and ground-contact time on running economy - Di Michele, R.; Merni, F. (Journal of Science and Medicine in Sport, 2014)
Objectives: Running economy is a key determinant of endurance performance, and understanding the biomechanical factors that affect it is of great theoretical and applied interest. This study aimed to analyse how the ground-contact time and strike pattern used by competitive runners concurrently affect running economy. Design: Cross-sectional. Methods: Fourteen sub-elite male competitive distance runners completed a 6-min submaximal running trial at 14 km h-1 on an outdoor track using their habitual strike pattern (n = 7 rearfoot strikers: average age, 25.3 years old (SD = 2.4); average weight, 64.7 kg (SD = 5.6); average height, 175.3 cm (SD = 5.2); n = 7 midfoot strikers: average age, 25.0 years old (SD = 2.8); average weight, 69.6 kg (SD = 4.0); average height, 180.1 cm (SD = 5.1). During the run, the oxygen uptake and ground-contact time were measured. Results: Midfoot strikers showed a significantly shorter (p = 0.015) mean contact time (0.228 s (SD = 0.009)) compared with rearfoot strikers (0.242 s (SD = 0.010)). Conversely, there was no significant difference (p > 0.05) between the groups with respect to mean oxygen uptake (midfoot strikers: 48.4 ml min-1 kg-1 (SD = 5.3); rearfoot strikers: 49.8 ml min-1 kg-1 (SD = 6.4)). Linear modelling analysis showed that the effect of contact time on running economy was very similar in the two groups, with a 1 ms longer contact time involving an approximately 0.51 ml min-1 kg-1 lower oxygen uptake. In contrast, when controlling for contact time, midfoot striking involved an approximately 8.7 ml min-1 kg-1 lower oxygen uptake compared with rearfoot striking. Conclusions: When adjusting the foot-ground contact biomechanics of a runner with the aim of maximising running economy, a trade-off between a midfoot strike and a long contact time must be pursued.